The influences Of Vee Diagram On Animal Ecology Lab To Learning Outcomes And Logical Thinking - Purwati Kuswarini Suprapto (EDUCATIO : Journal of Education, 2017)
During this time, the student is less understanding the significance of animal ecology lectures, so that students are less able to apply it in real of life. Animal ecology lecture consists of lectures and practicum. The purpose of this research was to increase knowledge of animal ecology and logical thinking of students using the diagram Vee on Animal Ecology lab. Research method was quasi experiment. The study population was student of prospective teachers Biology at 6th Semester as much as 9 classes taken courses Ecology animals, samples taken purposing sampling by 2 classes. This research was conducted by using a diagram Vee during practicum. Data obtained from the results of learning tests and logical thinking using the Test of Logical Thinking (TOTL). Data processing with the T test using SPSS. The results showed that there was influence using Vee diagram of the learning outcomes and logical reasoning and intellectual development of students.